Beneficial role of melatonin in protecting mammalian gametes and embryos from oxidative damage - Yun-wei PANG; Xiao-long JIANG; Shan-jiang ZHAO; Zi-qiang HUANG; Hua-bin ZHU (Journal of Integrative Agriculture, 2018)
Mammalian gametes and embryos are particularly vulnerable to oxidative stress-induced damage, which is mainly caused by reactive oxygen species (ROS) originating from normal metabolism and/or the external environment. Several researchers have implicated the role of oxidative stress in the activation of apoptosis, causing peroxidative damage to sperms/oocytes and inducing embryo fragmentation, arrest, or demise. Melatonin is a tryptophan derivative that is known for its powerful free radical-scavenging activity and broad-spectrum antioxidant property. Numerous studies have shown that melatonin and its metabolic derivatives can sequentially detoxify ROS in an antioxidant cascade, and modulate various antioxidant enzymes via its receptors to prevent radical-mediated damage. The identification of melatonin receptors in cumulus/granulosa cells, oocytes, and epididymal tissues implies that melatonin has protective actions on gametes and embryos. Enriching the semen extender or culture medium with melatonin significantly benefits sperm characteristics, improves oocyte maturation potential and quality, and enhances the developmental competence of preimplantation embryos. Certainly, further comparative studies are needed to show the unique antioxidant role and the advantage of melatonin in this field. This review summarizes the harmful effects of ROS and the beneficial role of melatonin against oxidative damage of gametes and embryos.